Auditory P300 event-related potentials in fibromyalgia patients - Yoldas, T; Ozgocmen, S; Yildizhan, H; Yigiter, R; Ulvi, H; Ardicoglu, O (Yonsei Univ Coll Medicine, 2003)
This study assessed the cognitive brain function measured by the cognitive P300 auditory event-related potentials (ERPs) in female fibromyalgia (FM) patients and compared the results with those from healthy age and education-matched controls. The relationship of the P300 potentials to the pain threshold of patients was also investigated The P300 component of the auditory ERPs were studied in 11 female FM patients and 10 age and education-matched healthy controls. None of the patients were taking antidepressants such as amitriptyline or serotonin-reuptake inhibitors. The P300 latencies of the patients were not significantly different whereas the N2P3 amplitudes were significantly lower than the controls. The P300 latencies in the patients negatively correlated with the total myalgic scores (TMS) (r=-0.73) and the control point scores (CPS) (r=-0.85). On the other hand, the P300 amplitudes showed a significant correlation with the TMS (r=0.61) and the CPS (r=0.60). There was no significant correlation between the anxiety and depression scores with the P300 latency or amplitudes. These results showed cognitive impairment, which was mainly expressed by the lower N2P3 amplitudes in patients with FM, and its clinical relevance requires further research.
Keywords: fibromyalgia; auditory event-related potentials; P300